Therapeutic agents for Alzheimer’s disease: a critical appraisal - Weinstock, Marta (Frontiers in Aging Neuroscience, 2024)
Alzheimer’s disease (AD) is the most common form of dementia. Mutations in genes and precursors of β amyloid (Aβ) are found in the familial form of the disease. This led to the evaluation of seven monoclonal antibodies against Aβ in subjects with AD, two of which were approved for use by the FDA. They caused only a small improvement in cognitive function, probably because they were given to those with much more prevalent sporadic forms of dementia. They also have potentially serious adverse effects. Oxidative stress and elevated pro-inflammatory cytokines are present in all subjects with AD and are well correlated with the degree of memory impairment. Drugs that affect these processes include TNFα blocking antibodies and MAPK p38 inhibitors that reduce cognitive impairment when given for other inflammatory conditions. However, their adverse effects and inability to penetrate the brain preclude their use for dementia. Rosiglitazone is used to treat diabetes, a risk factor for AD, but failed in a clinical trial because it was given to subjects that already had dementia. Ladostigil reduces oxidative stress and suppresses the release of pro-inflammatory cytokines from activated microglia without blocking their effects. Chronic oral administration to aging rats prevented the decline in memory and suppressed overexpression of genes adversely affecting synaptic function in relevant brain regions. In a phase 2 trial, ladostigil reduced the decline in short-term memory and in whole brain and hippocampal volumes in human subjects with mild cognitive impairment and had no more adverse effects than placebo.